Service Quality and Customer Experience on Customer Satisfaction at Fast Food Restaurants in Medan City - Atika Aini Nasution; Aan Nurhadi; M. Asyari Syahab (Universitas 17 Agustus 1945 Semarang, 2024)
Factors that can attract consumer interest in satisfying customers at fast food restaurants in Medan City include providing quality service. In addition to service quality, customer experience is also another factor that can attract consumer interest in buying. One thing that companies can do is to build a brand so that it will create brand equity. Based on the description above, the title of the study is,